2007
DOI: 10.1007/s10608-007-9145-y
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Blushing: No Overestimation of Negative Anticipated Interpersonal Effects, But a High-Subjective Probability of Blushing

Abstract: To explain blushing phobics' fearful preoccupation with blushing, this study investigated the anticipated consequences of blushing when considering the interpersonal influences of displaying a blush. Using a vignette study approach, participants (N = 48, mean age 20.47, and SD 4.44) with variable levels of fear of blushing were instructed to imagine that they did or did not blush in several situations, and were asked to indicate their expectations of an observer's judgment. Irrespective of their fear of blushi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…We postulate that it is worth distinguishing exaggerated expectations concerning the likelihood of an encounter with a feared stimulus (encounter expectancy bias) from exaggerated expectations concerning the likelihood of incurring aversive consequences of such an encounter (consequences expectancy bias). For example, a study by Dijk and de Jong (2009) demonstrated that blushing phobics did not overestimate the negative consequences of blushing. However, at the same time, these phobics expected to blush more often than did individuals who were characterized by lower levels of fear of blushing.…”
Section: Evidence For An Encounter Expectancy Bias In Fear Of Spidersmentioning
confidence: 99%
“…We postulate that it is worth distinguishing exaggerated expectations concerning the likelihood of an encounter with a feared stimulus (encounter expectancy bias) from exaggerated expectations concerning the likelihood of incurring aversive consequences of such an encounter (consequences expectancy bias). For example, a study by Dijk and de Jong (2009) demonstrated that blushing phobics did not overestimate the negative consequences of blushing. However, at the same time, these phobics expected to blush more often than did individuals who were characterized by lower levels of fear of blushing.…”
Section: Evidence For An Encounter Expectancy Bias In Fear Of Spidersmentioning
confidence: 99%
“…Dijk and colleagues (Dijk & de Jong, ; Dijk, de Jong, & Peters, ; Dijk, Voncken, & de Jong, ) recently developed a cognitive model to help explain why blushing‐fearful individuals live in fear of their blushes. They proposed that self‐focused attention leads to a perception of blushing, which elicits negative automatic thoughts about the social costs of blushing.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that self‐focused attention leads to a perception of blushing, which elicits negative automatic thoughts about the social costs of blushing. People who fear blushing appear to have a strong automatic association between blushing and negative social outcomes, and explicit expectations about the social costs of blushing (Dijk & de Jong, ; Glashouwer, de Jong, Dijk, & Buwalda, ). However, the beliefs that underlie these negative automatic thoughts are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Blushing is a common physiological response assumed to occur in situations in which people suddenly become conscious of themselves (Crozier 2006 ). While there is evidence that blushing is functional for interpersonal communication (e.g., Leary et al 1996 ; Dijk and de Jong 2009 ; Dijk et al 2011 ), people often experience their blushing as an undesirable response to the extent that they try to prevent or hide it (Shields et al 1990 ). For some individuals blushing is so unpleasant that they develop a fear of blushing (e.g., Mulkens et al 2001 ).…”
mentioning
confidence: 99%
“…That is, individuals with fear of blushing may fear being seen by others as incompetent, unlikeable, and unreliable (e.g., Bögels and Reith 1999 ; Dijk et al 2010 ; Dijk et al 2009 ). In previous studies, we have used vignettes to assess in individuals with fear of blushing their expectations of displaying a blush in several types of situations: after a social transgression, when being the center of attention, during the disclosure of something personal, and in circumstances in which people usually do not blush (de Jong and Peters 2005 ; de Jong et al 2006 ; Dijk and de Jong 2009 ; Dijk et al 2010 ). These studies showed that, compared to individuals with low fear of blushing, individuals with high fear of blushing anticipated heightened social costs of their blushing only in circumstances during which people usually do not blush.…”
mentioning
confidence: 99%